Пошаговое объяснение:
1)
= -2/3 * 6/7 - (-2/3х) + 2/7 + х =
-12/21 + 2/3х + 2/7 + х =
-4/7 + 2/3х + 2/7 + х =
1. 2/3х - 2/7
2)
= -х - 1/8 + 3/4 * 2 + 3/4х =
-х - 1/8 + 6/4 + 3/4х =
-х - 1/8 + 12/8 + 3/4х =
-1/4х + 11/8 = -1/4х + 1. 3/8
3)
= 7/8 * 4 - 7/8х - 3/4 - х =
28/8 - 7/8х - 6/8 - х =
-1. 7/8х - 22/8 =
-1. 7/8х - 2. 6/8 =
-1. 7/8х - 2. 3/4
4)
= -3/19 + х - 1/2х - 1/2 * 2/19 =
-3/19 + х - 1/2х - 1/19 =
1/2х - 4/19
5)
= -7/13 * 26/27 - 7/13х - 4/9 + х =
-7/1 * 2/27 - 7/13х - 4/9 + х =
-14/27 - 7/13х - 4/9 + х =
-14/27 - 7/13х - 12/27 + х =
6/13х - 26/27
1,5*10=15( кг)- сахара на 10 кг ягод